OLED: A New Display Technology (International Journal of Engineering and Computer Science, 2017)
OLEDs are a great breakthrough in display technology .Also a new promising technology with high expected profitability on the display market. They show low driving voltages in combination with unrestricted viewing angles, high color-brilliance, light weight, small film-thicknesses and low production costs. Organic light-emitting devices (OLEDs) operate on the principle of converting electrical energy into light, a phenomenon known as electroluminescence. This paper focuses on structure of OLED, how it works, comparison with other display and applications.